Magnetic Studies of Superconductivity in the Ga-Sn Alloy Regular Nanostructures - Marina V. Likholetova; Elena V. Charnaya; Evgenii V. Shevchenko; Min Kai Lee; Lieh-Jeng Chang; Yurii A. Kumzerov; Aleksandr V. Fokin (Nanomaterials, 2023)
For applications of nanolattices in low-temperature nanoelectronics, the inter-unit space can be filled with superconducting metallic alloys. However, superconductivity under nanoconfinement is expected to be strongly affected by size-effects and other factors. We studied the magnetic properties and structure of the Ga-Sn eutectic alloy within regular nanopores of an opal template, to understand the specifics of the alloy superconductivity. Two superconducting transitions were observed, in contrast to the bulk alloy. The transitions were ascribed to the segregates with the structures of tetragonal tin and a particular gallium polymorph. The superconducting-phase diagram was constructed, which demonstrated crossovers from the positive- to the common negative-curvature of the upper critical-field lines. Hysteresis was found between the susceptibilities obtained at cooling and warming in the applied magnetic field.